A REVIEW OF ANTIBACTERIAL POTENTIAL OF BANANGBANANG PLANT (Xylocarpus granatum J.Koenig) EXTRACT - Galuh Bela Pertiwi; I Gusti Agung Ayu Kusuma Wardani; Ni Made Dwi Mara Widyani Nayaka (Journal Pharmaceutical Science and Application, 2023)
Background: Xylocarpus granatum has been used traditionally by coastal communities to treat various diseases. It is known that this plant contains secondary metabolites with various pharmacological activities, including as an antibacterial. Objective: This review article aims to provide information regarding the potential antibacterial activity of banangbanang plants and to summarize the content of compounds that have antibacterial properties and their mechanism of action. Methods: The preparation of this article is through literature studies from various international journals and national journals obtained online by taking into account predetermined inclusion and exclusion criteria. Then it was selected and studied further to obtain data related to the antibacterial activity of banangbanang plants and the content of secondary metabolites that have potential as antibacterials. Result: The banang-banang plant, especially the leaves, roots, fruit, seeds, fruit flesh, fruit peels, stems and bark with its secondary metabolites can inhibit several bacterial species such as Staphylococcus epidermidis, Pseudomonas aeruginosa, Escherichia coli, Vibrio alginolyticus, Staphylococcus aureus, Shigella boydii , Proteus spp., Streptococcus pyogenes, Ralstonia solanacaerum, Propionibacterium acnes, Agrobacterium tumefaciens, Aspergillus paraciticus, Bacillus subtilis, Candida albicans, Pseudomonas fluorescence, Micrococcus luteus, Saccharomyces ceresiviae, Salmonella typhi, Vibrio alginoliticus and Aeromonas hydrophilla. The secondary metabolites of this plant that have potential as antibacterial are tannins, saponins, steroids, phenols, triterpenoids, flavonoids, alkaloids, terpenoids and glycosides which have their respective mechanisms of action as antibacterial agents. Conclusion: Secondary metabolites contained in each part of the Xylocarpus granatum plant are thought to have a role in its antibacterial activity. Keywords: Antibacterial; Mechanism of action; Secondary metabolite; Xylocarpus granatum J.Koenig.